Effects of dietary supplementation of chitosan on carcass composition and meat quality in growing Huoyan geese - Zhiguo Miao; Liping Guo; Yongliang Liu; Weixin Zhao; Jingzhou Zhang (Poultry Science, 2020)
This present study was conducted to investigate the effects of dietary supplementation of chitosan (CS) on carcass composition and meat quality in growing Huoyan geese. A total of 320 (28-day-old) growing Huoyan geese (sex balance) with similar body weight were randomly divided into the following 4 main groups: basal diet (control), basal diet + 100 mg/kg CS (CS100), basal diet + 200 mg/kg CS (CS200), and basal diet + 400 mg/kg CS (CS400) groups. Each group includes 4 replicates with 20 geese per replicate, and the feeding trail lasted for 4 wk. The results showed that the geese in CS200 group had lower abdominal fat percentage, b∗ value, shear force, crude fat content, and drip loss of breast and thigh muscle than those in the control group (P < 0.05). In addition, the CS200 group had higher glutamic acid, glycine, lysine, valine, total nonessential amino acids, total essential amino acids, total amino acids, C22:0, C16:1, C18:1, C20:1, C20:2, C20:5, total monounsaturated fatty acids concentration and polyunsaturated fatty acids (PUFA), and saturated fatty acids (SFA) ratio and lower total SFA, total PUFA concentration, and total n-6:n-3 ratio in breast muscle than the control group (P < 0.05). Taken together, these results indicated that addition of 200 mg/kg CS improved meat quality in growing Huoyan geese through altering slaughter performance, meat traits, amino acids, and fatty acids composition.